FIRM SIZE, AUDIT COMMITTEE, AND FIRM VALUE: AUDIT DELAY AS AN INTERVENING VARIABLE - Edi Saputra; Andika Patria; Siti Lestari (ACCOUNT: Jurnal Akuntansi, Keuangan dan Perbankan, 2026)
The purpose of this research is to test and analyze the effects of Firm Size and Audit Committee on Firm Value, as well as the intervening effect of Audit Delay on the relationship among them. The sample consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023, with 15 companies experiencing financial reporting delays of over 90 days. This study uses a variance-based structural equation model (SEM-PLS). The results in this study show that Firm Size and Audit Committee have no effect on Firm Value. The results of this study also indicate that Audit Delay mediates the relationship between Firm Size and Firm Value, but it does not mediate the relationship between Audit Committee and Firm Value.